The effects of a long wait for children’s dental general anaesthesia - SARAH NORTH, LESLEY E. DAVIDSON, ANTHONY S. BLINKHORN, & IAIN C. MACKIE (IAPD and Blackwell, 2007)
The purpose of this study was to monitor the effect of an interruption in a service for children who were scheduled to have dental extractions under general anaesthesia (GA).